Acts of Literature - Moi, Ruben; Fagertun, Thoralf (Nordlit, 2009)
Despite the fact that literary theory has sought new orientations since Derrida´s biblioblitz in the late 1960s and early 1970s, this article claims that the French philosopher's multiple approaches to literatureindubitably mark a shift in literary hermeneutics. Although the questioning of philosophy, language, aesthetic institutions, and genre solidities per se spurs much of his intellectual analysis, Derrida responds to a great diversity of what is normally termed literature in his writing. Derrida´s Acts of Literature presents a point of departure for this article, which traces his engagements with literature in large parts of his oeuvre. Throughout discussions of his many subversions of literary traditions and reflections of the extensive dispute that surrounds his work, the authors seek to demonstrate the significance of his interrogations for the field of literary interpretation.Selv om litteraturteorien har beveget seg i ulike retninger siden Derridas biblioblitz på slutten av 1960-tallet og begynnelsen av 1970-tallet, hevder denne artikkelen at den franske filosofens ulike tilnærminger til litteratur utvilsomt har forandret hermeneutikken. Til tross for at skepsis til filosofi, språk, estetiske uttrykksformer og sjangersoliditet utgjør mye av hans intellektuelle analyser, undersøker Derrida i sin skrivning en rekke ulike typer tekster som vi tradisjonelt sett karakteriserer som litteratur. Derridas Acts of Literature utgjør et springbrett for denne artikkelen som prøver å perspektivere undersøkelsene av litteratur i store deler av hans produksjon. Gjennom å diskutere hans mange oppgjør med litterære tradisjoner og å reflektere over den omfattende debatten hans arbeider har skapt, har forfatterne til hensikt å påvise hvilken betydning hans litterære undersøkelser kan ha for litterær fortolkning.
Keywords: Derrida; aesthetics; literature; literary theory